Disfunción familiar y su incidencia en el estado emocional en una adolescente de 13 años de edad de la Unidad Educativa Abdón Calderón Muñoz en la ciudad de Babahoyo - Valencia Pambabay, Nicole Stefania (2023)
The present case study has as its theme: Family dysfunction and its incidence in the emotional state in a 13-year-old adolescent from the "Abdón Calderon Muñoz Educational Unit" in the city of Babahoyo and as an objective, to analyze the incidence of dysfunction family on the emotional state of a 13-year-old adolescent. To carry out the case study, several techniques were used, among them we have: observation, semi-structured interview, clinical history, projective techniques, psychometric tests, Beck Depression Inventory-II (BDI-II). It should be noted that there are different factors that influence the emotional state of the adolescent, one of them and the most evident being her family environment. That is to say, the family is the fundamental pillar in every human being, since if it does not fulfill its functions and basic needs, such as protecting the lives of their loved ones, love, food, it is considered a dysfunctional family, for which a dysfunctional aspect due to the fact that the adolescent does not live with her parents and it is important to add that she is under the care of her grandmother, all these detected situations are affecting the state of mind and have an impact on causing problems in her behavior. The adolescent presents criteria for the diagnosis of Major Depressive Episode, to approach the patient, the psychotherapeutic intervention was carried out through Cognitive Behavioral Therapy (CBT) because the adolescent presents distorted thoughts, suicidal, low self-esteem, sadness.